Is It Asleep? - Tallec, Olivier; Shugaar, Antony (Minneapolis, MN : Gecko Press, 2025)
Squirrel and his best friend, Pock the mushroom, learn about the cycle of life and death when they discover a blackbird lying still on the path.
new kids book 2025 fall.
Ages 4-7.
Grades 4-6.
Translated from French.
Keywords: Life cycles -- Fiction; Squirrels -- Fiction; Mushrooms -- Fiction; Death -- Fiction; Picture books